An Econometric Study Of The Impact Of Oil Price Fluctuations On The Algerian Dinar Exchange Rate During The Period 1990-2020 (Revue El-Wahat pour les Recherches et les Etudes, 2025)
This Study Aims To Find Out The Impact Of Oil Price Fluctuations On The Exchange Rate Of The Algerian Dinar During 1990 To 2020, As Our Study Relied On The Historical Descriptive Approach In The Theoretical Side Of The Study And On The Analytical Approach On The Applied Side By Analyzing The Curves And Tables Of The Study Extracted From The Eviews 12 Program .Our Study Concluded That The Time Series Of Oil Prices And The Exchange Rate Are Not Stable At The Level According To The ADF And PB Test, And Showed That There Is No Common Integration Relationship Between Oil Prices And The Exchange Rate According To The Statistical Impact Test, In Addition To The Absence Of A Causal Relationship In The Trend From Oil Prices Towards The Exchange Rate According To The Granger Causality Test As Well As The Exchange Rate To Oil Prices.Keywords: Oil Price, Exchange Rate,  ADF , VAR, Economy Of Algeria.